Epidermal growth factor polymorphism most prevalent in stage II cervical carcinoma - Kevin Dominique Tjandraprawira; Ramdan Panigoro; Yudi Mulyana Hidayat; Herman Susanto; Edhyana Sahiratmadja (Universa Medicina, 2014)
Background    Cervical cancer ranks second among female cancers worldwide and is widely associated with human papilloma virus (HPV) infection. However, HPV infection progression is influenced by various host factors. Epidermal growth factor (EGF) is a host factor important for proper epithelial proliferation and development, and may play a role in cervical cancer progression. A functional A61G polymorphism in the EGF gene has been hypothesized to alter EGF concentration in vivo with increasing guanine content associated with greater EGF level. However, a map of A61G polymorphism distribution is not available for any population, including Indonesia. This study aims to determine the distribution of EGF A61G polymorphism among cervical cancer patients at Dr. Hasan Sadikin General Hospital.MethodsA retrospective cross-sectional study was conducted between July-November 2010. Included were 61 cervical cancer patients of various stages at Dr. Hasan Sadikin hospital, who had previously undergone blood sample collection, DNA isolation and finally genotyping for EGF gene using Illumina BeadXpress®. Chi-square test was used to analyse the data. ResultsThe EGF A61G polymorphism was exhibited by 88.5% of patients (as genotypes A/G and G/G). The majority of patients with this polymorphism were of moderate severity (FIGO stage II and III, 42.6% and 38.1% respectively). Patients with the polymorphism but with the lightest severity (FIGO stage I) accounted for 22.2% of the population. ConclusionEGF A61G polymorphism affected the majority of cervical cancer patients and that once stratified, the patients showed intermediate severity in terms of their cancerous growth.